Spatial and temporal assessment of gaseous pollutants in the Highveld of South Africa - Alexandra S. Lourens; Johan P. Beukes; Pieter G. van Zyl; Gerhardus D. Fourie; Johanna W. Burger; Jacobus J. Pienaar; Colin E. Read; Johan H. Jordaan (South African Journal of Science, 2011)
Diverse natural and anthropogenic activities in the Highveld of South Africa contribute to elevated levels of inorganic and organic gaseous pollutant species. The primary aims of this investigation were to determine spatial and temporal distributions of nitrogen dioxide (NO2), sulphur dioxide (SO2) and ozone (O3), as well as benzene, toluene, ethylbenzene and xylene (BTEX) in this area. Sampling was conducted on a monthly basis for a year at eight strategically selected sites. The highest NO2, SO2 and BTEX concentrations were measured at sites with significant local sources and/or sites impacted by more remote sources, as indicated by overlay back trajectories. O3 concentrations were found to be lower at sites with high levels of NO2, SO2 and BTEX. NO2 and SO2 peaked during winter, while O3 peaked in spring. NO2 and SO2 temporal concentration variations were ascribed to differences in seasonal meteorological conditions, as well as additional sources in winter. The O3 peak coincided with a seasonal CO peak, which was identified as an important precursor for O3 formation. No distinct seasonal trend was observed for BTEX. The annual average concentrations for SO2, NO2, O3 and benzene were below the South African annual standards at all sites.